Rethinking Past and Present in Cuba Essays in memory of Alistair Hennessy - Kapcia, Antoni (University of London Press, 2021)
This collection of essays and research articles has been designed, by its breadth of expertise and discipline, to pay suitable homage to the seminal influence and contribution made by the late Alistair Hennessy towards the development of Cuban studies. For that reason, it includes a judicious mixture of the old and the new, including several of the leading and internationally well-established experts on Cuban history, politics and culture, but also some up-and-coming researchers in the field; that mixture and the combination of topics (some addressing the past directly, others assessing the present within a historical context) reflects Hennessy's own cross-disciplinary and open-minded approach to the study of the history of Cuba.